The Implementation of Amar Ma'ruf Nahi Munkar Qadi al-Baqilany : Hassan Hanafi’s Phenomenological Hermeneutic Approach - Akhmad Jazuli Afandi; Islam Saad Mohamed Abdelmoneim (Tribakti: Jurnal Pemikiran Keislaman, 2023)
This article aims to review the application of the concept of Amar Ma'ruf Nahi Munkar Qadi al-Baqilany using Hassan Hanafi's phenomenological hermeneutics as an analytical approach. The socio-political and thought conditions of al-Baqilany's time became a problem in itself. The diversity of society that is not only from the Arab community also raises problems that require special handling. Qadi al-Baqilani had a view of Amar Ma'ruf Nahi Munkar who could respond to the realities of the time. This research uses qualitative methods with the type of literature study. The choice of Hasan Hanafi's phenomenological hermeneutics as an approach aims to deepen the study so as to get a complete picture of the real implementation of Amar Ma'ruf Nahi Munkar Qadi al-Baqilany. The researcher's analysis includes socio-historical conditions, texts, reality and people's consciousness. The main instruments are reduction data, display data and conclusions. The results show that a) the socio-historical, political and thought of society is very diverse. There was a lot of poverty and misthinking by the Mu'tazilites as key holders of the madhhab in government. So that the implementation carried out by Al-Baqilany is to conduct scientific debates to several schools or schools, especially the Mu'tazilites, Jahmiyah and Shia in the place provided by the government. And also by contradicting the Roman king, b) the incorporation of reason and naqli in every argument, c) the use of linguistic elements needed in his works and debates, d) the use of communicative, systematic, simple and understandable language at every level of his works and e) the existence of mass awareness efforts.